Some Connections of Africa and the U.S.A in American World Literature (International Journal of Scientific Research and Management (IJSRM), 2019)
The plots in some novels by Nathaniel Hawthorne, Toni Morrison, Maya Angelou and Paule Marshall, to name but a few, remind the African readers of some sociological realities on the black continent. That interconnection of Africa and the U.S.A., through literature, reinforces the idea of American literature as world literature. If the U.S.A. was a child, we could assert that his or her parents are Africa and Europe thanks to their irrefragable contributions to the making of the country. There is undoubtedly an interconnection of Africa and the USA in quite a few fields, especially in works of fiction Kimberly Crenshaw’s feminist theory of intersectionality is very much present in quite a few American novels. In Nathaniel Hawthorne’s The Scarlet Letter, the ostracism of Hester Prynne, a wife in seventeenth-century Puritan America, after she gave birth to an illegimate child, is tantamount to a “social death” in Africa, where women are still required to be paragons of virtue, especially when they are married. Under no circumstances, should espoused women, in many African societies have paramours and indulge in such a turpitude. Obinna Udenwe expounds on that issue in her short story “Bedfellows.” In Maya Angelou’s Gather Together in My Name, Rita’s early pregnancy is similarly a poignant problem in Africa, where some girls are married as young as 12 or 13. That situation recurs in Toni Morrison’s The Bluest Eye, with Pecola who is impregnated at 12. As for Paule Marshall, her novel Praisesong for a Widow is full of African cultural representations and supernatural rites like the ceremony of “lave tête”.